Memperlengkapi Penatua dan Diakon Melalui Pembinaan Berkelanjutan - May Linda Sari (Sekolah Tinggi Teologi Gereja Kalimantan Evangelis, 2024)
Community development is an effort to equip the congregation in holistic service, faith in God, and spiritual maturity. One of the locus of development activities is the GKE Cempaga Hulu Resort. The development was held as collaboration of the Resort GKE Cempaga Hulu and STT GKE. This development aims to increase the understanding of Elders and Deacons regarding the GKE Church Order and church teachings. The methods used were lectures and questions and answers. The result of the PkM is that the Elders and Deacons have a good understanding of the GKE Constitutions as a guide in the ministry. Meanwhile, an understanding of the correct church teachings needs to be continuously conveyed to the congregation, because there are many theological problems among the congregation. In responding to this, churches and theological schools must work together to make continuous development programmes.